Visceral adipose tissue and residual cardiovascular risk: a pathological link and new therapeutic options - Cesaro, Arturo; De Michele, Gianantonio; Fimiani, Fabio; Acerbo, Vincenzo; Scherillo, Gianmaria; Signore, Giovanni; Rotolo, Francesco Paolo; Scialla, Francesco; Raucci, Giuseppe; Panico, Domenico; Gragnano, Felice; Moscarella, Elisabetta; et al. (Frontiers in Cardiovascular Medicine, 2023)
Obesity is a heterogeneous disease that affects almost one-third of the global population. A clear association has been established between obesity and cardiovascular disease (CVD). However, CVD risk is known to be related more to the local distribution of fat than to total body fat. Visceral adipose tissue (VAT) in particular has a high impact on CVD risk. This manuscript reviews the role of VAT in residual CV risk and the available therapeutic strategies for decreasing residual CV risk related to VAT accumulation. Among the many pathways involved in residual CV risk, obesity and particularly VAT accumulation play a major role by generating low-grade systemic inflammation, which in turn has a high prognostic impact on all-cause mortality and myocardial infarction. In recent years, many therapeutic approaches have been developed to reduce body weight. Orlistat was shown to reduce both weight and VAT but has low tolerability and many drug-drug interactions. Naltrexone-bupropion combination lowers body weight but has frequent side effects and is contraindicated in patients with uncontrolled hypertension. Liraglutide and semaglutide, glucagon-like peptide 1 (GLP-1) agonists, are the latest drugs approved for the treatment of obesity, and both have been shown to induce significant body weight loss. Liraglutide, semaglutide and other GLP-1 agonists also showed a positive effect on CV outcomes in diabetic patients. In addition, liraglutide showed to specifically reduce VAT and inflammatory biomarkers in obese patients without diabetes. GLP-1 agonists are promising compounds to limit inflammation in human visceral adipocytes.